(untitled) (Fiep Bulletin - online, 2019)
From the 80’s there was growth in the performance of physical education professionals who work in custom work.Note that the financial figures are extremely attractive, however, some professionals do not have the broad view of theorganization and planning of your business is critical to success in personal trainer career. When interviewing 25 professionalsworking as a personal trainer, there was low or absence of fundamental multidisciplinary and interdisciplinary knowledge for themanagement of a company, which directly implies the lowest of new students capture potential and, consequently, in a lowerreturn financial, requiring them to act in other areas. Thus, it appears that the incentive to search for knowledge in the areas ofadministration, management, planning and entrepreneurship are essential to a dynamic and successful personal trainer career.